Infection and failure rates following total hip arthroplasty for septic arthritis: a case-controlled study. Issue 1 (January 2018) - Papanna, Madhavan C.; Chebbout, Ryad; Buckley, Simon; Stockley, Ian; Hamer, Andrew
Introduction: Total hip arthroplasty (THA) is performed as a 2-stage or single stage procedure in patients with a history of septic arthritis of the native hip joint. The decision is based on whether the infection is active or quiescent in the joint. The aim of this study was to compare the outcomes of total hip arthroplasty for septic arthritis of the native hip to a control series of patients treated for primary osteoarthritis of the hip with standard THA. Methods: Between March 2000 and March 2013, 18 cases of septic arthritis of the hip treated with THA were retrospectively identified. During the same time period, 18 control cases of THA for degenerative osteoarthritis were identified. Cases and controls were comparable in age, gender, body mass index, type of anaesthesia and American Society of Anesthesiologists score. Results: 11 and 7 cases received 2-stage and single stage total hip arthroplasty respectively for septic arthritis. There was a mean interval of 4 months between 1 st and 2 nd -stage operations. Cases and controls were followed up for a mean of 70 and 72 months respectively. There was no reinfection or implant failure in the cases, and comparable functional outcomes between cases and controls. Conclusions: Two-stage and single-stage THA for active and quiescent native hip infection respectively, achieved similar outcomes to THA for primary osteoarthritis in controls.